Blood Circulating miRNAs as Cancer Biomarkers for Diagnosis and Surgical Treatment Response - Filipów, Samantha; Łaczmański, Łukasz (Frontiers in Genetics, 2019)
miRNAs can function as potential oncogenes or tumor suppressors. Altered expression of these molecules was correlated with the occurrence of many cancer diseases and therefore they are considered a molecular tool for noninvasive cancer diagnosis and prognosis. We searched for analyses concerning expression of blood circulating miRNA in cancer patients. The studies comprised of at least two miRNA expression measurements: before and after the surgical therapy were considered. We summarized latest reports on evaluation of the efficiency of anticancer therapy through observation of changes in expression of miRNA circulating in blood of patients treated with surgery alone. 21 research studies were identified. 31 different miRNAs were pointed out as potential both diagnostic and treatment response biomarkers since their deregulated expression before therapy returned to normal after receiving the treatment. Published data revealed a potential of circulating miRNA to become a tool giving a clinical follow up information on the efficiency of applied therapy. However, more observational studies on post-operative circulating miRNA expression changes are necessary.